Burkina Faso : The Budget as Centerpiece of PRSP Implementation, Public Expenditure Review - World Bank (Washington, DC, 2012)
This Public expenditure Review (PER) builds on budget procedures and budget implementation, following three years of Poverty Reduction Strategy Paper (PRSP) implementation. It reviews progress in budget management, and budget priorities, proposes a closer institutional integration of programmatic budgeting with the PRSP process, and reviews recent developments, and expenditure policies in the health, and education sectors. The PER focuses on the budget process, which is formally transparent, but reallocations made throughout the budget preparation process are not always based on clear criteria. Budget information is available to the government and donors during the year, but not to the wider public, who has to rely on PRSP progress reports, and budget execution reports. Overall, further progress is needed in providing timely information to the public on budget preparation, and execution. Notably, the PRSP process and the availability of HIPC funds, led to a substantial increase of expenditure in priority areas (education, health, rural development) and similarly, core priority areas (primary education, primary health, and rural development), doubling per-capita spending between 1998 and 2002. However, little of the additional spending was for recurrent expenditure, raising concerns as regards the balance between investments, and operational expenditure. The PRSP process has not generated significant additional resources in real terms. However, it has been accompanied by a shift from project to budget support. Nonetheless, the limited predictability of budget support within fiscal years has caused difficulties for expenditure and cash management. Recommendations include: Systematic review on the level of recurrent and investment spending in priority areas, based on budget execution data for 1998-2003; implementation of recommendations on technical assistance provision, to improve programming and monitoring of foreign-financed investment spending; improvement on the functioning of inter-ministerial working groups, to ensure consistency between PRSP and sectoral programs, to open these to civil society, private sector, and donor participation; and, improved efficiency of ex-ante control, adopting a price referential, a decree on the "morality" of expenditure, and, a revision of the required documentation's nomenclature.